LITERATURE REVIEW: EFEKTIFITAS LATIHAN FIFA 11+ WARM-UP UNTUK MENURUNKAN RESIKO CEDERA HAMSTRING PADA PEMAIN FUTSAL AMATIR - Andri Wijaya (2021)
Objective: The high rate of hamstring injuries is influenced by the lack of knowledge and proper technique during warm-up by amateur futsal players. This study aims to examine literature, journals, articles or research results with the topic of the effectiveness of the FIFA 11+ Warm-Up exercise to reduce the risk of hamstring injury in amateur futsal players. Methods: Search for sources of literature, journals, articles, research results in several databases such as Google Scholar, Science Direct, Elsevier, PEDro, PubMed using certain keywords in the 2016-2021 period. From the results of the literature search, 10 articles were obtained and only 6 articles met the source inclusion criteria. The methodological quality assessment of 6 articles was assessed with the Scimago Journal & Country Rank (SJR). Analysis of the 6 journals was carried out based on the suitability of the topic, the research methods used, samples, interventions, instruments/parameters, and the results of each article. Results: After reviewing the literature as many as 6 articles showed that the FIFA11+ Warm-Up training program has been proven to be effective in reducing the risk of hamstring injuries. Conclusion: The FIFA 11+ Warm-Up exercise can significantly reduce the risk of hamstring injury in amateur futsal players.